Morphological Changes of Salicylic Acid Application on Pepper (Capsicum annuum L.) Seedling under Cold Condition - Mohammed Ahmed Ahmed; Muhemet Zeki Karipçin; Fikret Yaşar (International Journal of Secondary Metabolite)
This project was developed to investigate the contribution of salicylic acid (SA) to the development of pepper seedlings grown in low temperature (0 0C) conditions. The research was carried out in the controlled plant growing cabinet in the research- investigation area of the Department of Horticulture, Faculty of Agriculture, Siirt University. As a vegetable material, Urartu F1 pepper type (capia) which is used in greenhouse cultivation has been used. As a dose of different salicylic acid; 0.01 and 0.05 mmol doses were applied. The dose of 0 mmol salicylic acid was used as a control group. Application frequency; It was applied 1 time, 2 times and 3 times.3 different cold application times were also investigated; 24 hours, 48 hours and 72 hours. The experiment was designed in randomized plots and 3 replications. In the pepper seedlings Rate of Lost Seedling Weight (ROLSW) and Rate of Lost Seedling Length (ROLSL) were investigated. At the end of the research; Both SA applications increased the ROLSW rate according to the control. The application of 0.01 ppm was the SA application with the highest ROLSW rate. The application of 0.01 ppm SA also increased the ROLSL rate compared to the control. The highest ROLSW and ROLSL rates were obtained from 24-hour cold application. There was no statistically significant difference between the frequencies of application.